A stabilization approach for mesh-free simulations of systems developing shocks or extreme strain localizations. (February 2015) - Pimprikar, N.; Sarkar, S.; Devaraj, G.; Roy, D.; Reid, S.R.
Abstract: A new stabilization scheme, based on a stochastic representation of the discretized field variables, is proposed with a view to reduce or even eliminate unphysical oscillations in the mesh-free numerical simulations of systems developing shocks or exhibiting localized bands of extreme deformation in the response. The origin of the stabilization scheme may be traced to nonlinear stochastic filtering and, consistent with a class of such filters, gain-based additive correction terms are applied to the simulated solution of the system, herein achieved through the element-free Galerkin method, in order to impose a set of constraints that help arresting the spurious oscillations. The method is numerically illustrated through its applications to inviscid Burgers' equations, wherein shocks may develop as a result of intersections of the characteristics, and to a gradient plasticity model whose response is often characterized by a developing shear band as the external load is gradually increased. The potential of the method in stabilized yet accurate numerical simulations of such systems involving extreme gradient variations in the response is thus brought forth. Highlights: A stabilization scheme for systems with high local gradient variations is proposed. The scheme has a stochastic basis and draws on the theory of nonlinear filtering. Unphysical oscillations are arrested by conditioning on a zero-mean noise process. The scheme is numerically tested on Burger׳s equation & a gradient plasticity model.